Preparation method of high-thermal-conductivity Cf / SiC-ZrB2-Diamond composite material and high-thermal-conductivity Cf / SiC-ZrB2-Diamond composite material

By introducing ZrB2 and diamond particles into ultra-high temperature modified continuous carbon fiber reinforced silicon carbide ceramic matrix composite material, and generating a silicon carbide protective layer, combined with liquid silicon permeation reaction, the problem of poor thermal conductivity of the composite material is solved, achieving the improvement of high thermal conductivity and strength.

CN119797948AActive Publication Date: 2025-04-11SDIC CERAMIC MATRIX COMPOSITES RES INST (XIAN) CO LTD

Patent Information

Application Number
CN202411939483.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The thermal conductivity of existing ultra-high temperature modified continuous carbon fiber reinforced silicon carbide ceramic composites is poor, resulting in the material being easily ablated and the thermal conductivity is weakened in harsh thermal stress environments.

Method used

By depositing a pyrolytic carbon layer and a SiC layer in the prefabricated body, combining vacuum pressure immersion and ultrasonic impregnation technology, ZrB2 and diamond particles are introduced, and a silicon carbide protective layer is formed on the diamond surface. Finally, a high thermal conductivity Cf/SiC-ZrB2-Diamond composite material is prepared by liquid-silicon permeation reaction.

Benefits of technology

The thermal conductivity of the composite material is significantly improved, and the strength reaches 257MPa, ensuring the high-temperature service life and ablation resistance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797948A_ABST
    Figure CN119797948A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a composite material, in particular to a preparation method of a high-thermal-conductivity Cf / SiC-ZrB2-Diamond composite material and the high-thermal-conductivity Cf / SiC-ZrB2-Diamond composite material, and overcomes the defects that in the prior art, diamond particles in a prefabricated body are not protected, the porosity of a C / SiC-Diamond composite material is high, and improvement of the thermal conductivity of the composite material is not facilitated. According to the preparation method, a pyrolytic carbon layer and a SiC layer are deposited on the surface of a carbon fiber preform, a shielding layer containing ultra-high-temperature ceramic is formed on the surface of a fiber bundle by impregnating resin-based slurry, then diamond particles are introduced by combining vacuum pressure impregnation and ultrasonic impregnation, and a silicon carbide protection layer is prepared on the surfaces of the impregnated particles. Then, phenolic carbon is introduced into the modified phenolic resin, and the high-thermal-conductivity Cf / SiC-ZrB2-Diamond composite material is prepared through an osmotic reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a composite material, and in particular to a high thermal conductivity C f / SiC-ZrB 2 -Diamond composite material preparation method and high thermal conductivity C f / SiC-ZrB 2 -Diamond composite material. Background Art

[0002] Ultra-high temperature modified continuous carbon fiber reinforced silicon carbide (C f C / SiC ceramic matrix composites have excellent high temperature resistance, oxidation resistance, ablation resistance and mechanical properties. They are mainly used in thermal protection components above 2000℃ and are considered to be ideal candidate materials for hot end components of future aerospace vehicles. However, their thermal conductivity is poor. The literature "Sufang Tang, Jingyi Deng*, Shijun Wang, Wenchuan Liu, Comparison of thermal and ablation behaviorsof C / SiC composites and C / ZrB 2 -SiC composites[J].Corrosion Science 51(2009)54-61”, the ultra-high temperature modified continuous carbon fiber reinforced silicon carbide ceramic matrix composite used is C / ZrB 2 -SiC composite materials, whose room temperature thermal conductivity in the thickness direction is lower than 12W / (m·K), seriously affects their service life and range. When the components are in a harsh thermal stress environment during service, due to the poor thermal conductivity of the material, thermal protection can only be performed by passive ablation of the material matrix. As the material ablates, the thermal protection effect weakens and the matrix will also crack or even crack and fail. In order to solve the problem of poor thermal conductivity of ultra-high temperature modified continuous carbon fiber reinforced silicon carbide ceramic matrix composites, the thermal conductivity of the material can be improved by matrix modification, so that the heat received by the material can be quickly conducted during service, so as to improve the material's operating temperature range and ablation resistance.

[0003] The thermal conductivity of diamond depends on the propagation of carbon atom vibration. Due to the high covalent bond energy between atoms, the atomic vibration energy is transmitted quickly and attenuated little. Its thermal conductivity at room temperature can reach up to 2000W / (m·K). In addition, diamond has a low thermal expansion coefficient and density, and the material strength will not be affected by thermal stress in a high temperature environment. Therefore, modifying ultra-high temperature modified continuous carbon fiber reinforced silicon carbide ceramic matrix composites with diamond can effectively improve the thermal conductivity of the material.

[0004] The Chinese patent with publication number CN109704776A introduces diamond into the preform by laser drilling combined with impregnation, and then uses RMI technology to prepare C / SiC composite materials, which effectively improves the thermal conductivity of the composite materials. However, laser drilling destroys the structure of the composite materials and affects their strength. In addition, in the literature "Jingxin Li, Yongsheng Liu, ChaoChen, Yu Pan, Jing Wang, Ning Wang, Effect of diamond content on microstructure and properties of C / SiC-diamond composites [J]. Diamond and Related Materials, 2020, 107902", Jingxin Li et al. introduced diamond with a particle size of 1 μm as a thermal conductive filler into the preform by vacuum repeated impregnation, and then prepared a C / SiC-Diamond composite material with a thermal conductivity of 14.68W / (m·K) by reactive infiltration. Compared with the C / SiC composite material prepared by chemical vapor infiltration (CVI) (thermal conductivity of 5-6W / (m·K)), its thermal conductivity is nearly doubled. However, the above method lacks protection for the diamond particles inside the preform before reactive infiltration (RMI). At the same time, the porosity after RMI is high, which is not conducive to the improvement of the thermal conductivity of the composite material. Summary of the invention

[0005] The purpose of the present invention is to solve the problems in the prior art that the diamond particles inside the preform lack protection and the porosity of the C / SiC-Diamond composite material is high, which is not conducive to improving the thermal conductivity of the composite material, and to provide a high thermal conductivity C f / SiC-ZrB 2 -Diamond composite material preparation method and high thermal conductivity C f / SiC-ZrB 2 -Diamond composite material.

[0006] To achieve the above objectives, the technical solutions provided by the present invention are as follows:

[0007] A high thermal conductivity C f / SiC-ZrB 2 The method for preparing the diamond composite material is special in that it comprises the following steps:

[0008] S1, a pyrolytic carbon layer and a SiC layer are sequentially deposited on the prepared preform to obtain a semi-dense porous C f / SiC preform;

[0009] S2, adding ZrB to the phenolic resin solution 2 The particles or SiC particles are ball-milled to obtain a first slurry;

[0010] S3, using the first slurry to treat the semi-dense porous C obtained in step S1 f / SiC preform is subjected to vacuum pressure impregnation, curing and cracking treatment in sequence;

[0011] S4, using the preform treated by the second slurry in step S3 to perform ultrasonic impregnation, curing and cracking treatment in sequence to obtain a preform filled with ultra-high temperature ceramics and diamond matrix; the second slurry is prepared by adding ZrB 2 The particles and diamond particles are mixed uniformly to obtain;

[0012] S5, preparing a silicon carbide protective layer containing diamond particles on the surface of the ultra-high temperature ceramic and diamond substrate filled in the preform;

[0013] S6, immersing the preform treated in step S5 into a phenolic resin solution modified with a metal salt, then taking it out and carbonizing it to obtain C / SiC-ZrB 2 -Diamond-C porous preform; the metal salt is a nickel-containing metal salt or a copper-containing metal salt;

[0014] S7, the C / SiC-ZrB obtained in step S6 2 -Diamond-C porous preform undergoes liquid silicon infiltration reaction to obtain high thermal conductivity C f / SiC-ZrB 2 -Diamond composite material, completed preparation.

[0015] Furthermore, step S5 is specifically as follows:

[0016] S5.1, adding 2-5 vol.% of 3-5 μm diamond particles to liquid polycarbosilane, stirring and dispersing to obtain a third slurry, immersing the preform obtained in step S4 into the third slurry under vacuum conditions, maintaining the vacuum conditions for 0.5-1 hour, then pressurizing, and taking out after maintaining the pressure at 0.5 MPa-1.4 MPa for 0.5-1 hour;

[0017] S5.2, curing the preform processed in step S5.1 in a vacuum environment at a temperature of 120-180° C. for 2-6 hours, and then maintaining the temperature at 900-1200° C. for 1-3 hours in a vacuum environment for cracking treatment.

[0018] Furthermore, step S6 is specifically as follows:

[0019] S6.1, using phenolic resin powder and its solvent to prepare a phenolic resin solution with a mass fraction of 20%-50%, adding a metal salt with a mass fraction of 1%-5% of the phenolic resin powder, stirring until the metal salt is completely dissolved, to obtain a fourth slurry; the solvent is ethanol or acetone; the metal salt is nickel chloride, cupric chloride, nickel nitrate or cupric nitrate;

[0020] S6.2, immersing the preform treated in step S5 into the fourth slurry under vacuum conditions, maintaining the vacuum conditions for 0.5-1 hour, then pressurizing, and taking out after maintaining the pressure at 0.5 MPa-1.4 MPa for 0.5-1 hour;

[0021] S6.3, curing the preform treated in step S6.2 at 100-150° C. for 2-6 hours, and then maintaining the temperature at 900-1200° C. for 1-3 hours in a vacuum environment for cracking treatment;

[0022] S6.4, repeating 1-3 rounds of steps S6.2 to S6.3, and then heat treating the preform at 1500-1600°C for 1-3 hours under a vacuum environment to obtain C / SiC-ZrB 2 -Diamond-C porous preform.

[0023] Further, step S7 is specifically as follows:

[0024] The C / SiC-ZrB obtained in step S6 is wrapped with silicon powder 2 -Diamond-C porous preform, then wrapped with graphite paper, and then C / SiC-ZrB 2 -The Diamond-C porous preform is placed in a siliconizing furnace and subjected to liquid silicon infiltration reaction for 30-120 minutes at 1500-1600℃ vacuum environment to obtain high thermal conductivity C / SiC-ZrB 2 -Diamond composite material, completed preparation.

[0025] Furthermore, step S3 is specifically as follows:

[0026] S3.1, under vacuum conditions, the semi-dense porous C f / The SiC preform is immersed in the first slurry, and the vacuum condition is maintained for 0.5-1 hour, and then pressurized, and taken out after maintaining the pressure at 0.5MPa-1.4MPa for 0.5-1 hour;

[0027] S3.2, curing the impregnated preform at 100-150° C. for 2-6 hours, and then maintaining the temperature at 900-1200° C. for 1-3 hours in a vacuum environment for cracking treatment.

[0028] Further, step S4 is specifically as follows:

[0029] S4.1, under vacuum conditions, immerse the preform treated in step S3.2 into the second slurry for 0.5-1 hour, place the preform and the second slurry in an ultrasonic disperser for ultrasonic immersion and stirring for 10-30 minutes, transfer the preform and the second slurry to a pressure impregnation tank, seal and pressurize, and take out after maintaining the pressure at 0.5MPa-1.4MPa for 0.5-1 hour; the second slurry is prepared by adding ZrB 2 The particles and diamond particles are mixed uniformly to obtain;

[0030] S4.2, curing the preform treated in S4.1 at 100-150°C for 2-6 hours, and then maintaining the temperature at 900-1200°C for 1-3 hours in a vacuum environment for cracking to obtain a preform filled with ultra-high temperature ceramics and a diamond matrix.

[0031] Furthermore, in step S4, the preparation method of the second slurry is specifically as follows:

[0032] Phenolic resin powder and its solvent are weighed according to the ratio to prepare a phenolic resin solution with a mass fraction of 15%-30%. The solvent is ethanol or acetone. ZrB with a particle size of 2-5μm is added to the phenolic resin solution. 2 particles and 3-6 μm diamond particles, stirred for 1-1.5 hours, and then ultrasonically treated for 1-1.5 hours, and the stirring and ultrasonic treatment were repeated to obtain a second slurry, wherein ZrB 2 The volume ratio of ZrB particles to diamond particles is 1:1. 2 The total volume of the particles and the diamond particles accounts for 6-12 vol.% of the total volume of the second slurry;

[0033] In step S1, the thickness of the pyrolytic carbon layer is 300-600 nm; the thickness of the SiC layer is 1-4 μm;

[0034] In step S2, the ZrB 2 Or the particle size of SiC is 0.1-1 μm, and the mass is 2%-15% of the phenolic resin solution; the mass fraction of the phenolic resin solution is 10%-20%, and the solvent is ethanol or acetone.

[0035] Further, in step S1, the thickness of the pyrolytic carbon layer is 500 nm, and the thickness of the SiC layer is 2-3 μm;

[0036] In step S2, the mass fraction of the phenolic resin solution is 15%, and ZrB is added to the phenolic resin solution. 2 Particles, ZrB 2 The particle size of the particles is 0.5 μm and the mass is 5% of the phenolic resin solution;

[0037] In step S3.1, the vacuum condition is maintained for 0.5 hours, and then pressurized, and the pressure is maintained at 0.8 MPa for 0.7 hours before being taken out;

[0038] In step S3.2, the impregnated preform is cured at 120°C for 4 hours, and then kept at 1000°C for 2 hours in a vacuum environment for cracking treatment;

[0039] In step S4.1, the preform treated in step S3.2 is immersed in the second slurry for 0.5 hours, the preform and the second slurry are placed in an ultrasonic disperser for ultrasonic immersion and stirring for 20 minutes, the preform and the second slurry are transferred to a pressure impregnation tank, sealed and pressurized, and taken out after maintaining a pressure of 0.9 MPa for 0.5 hours;

[0040] In step S4.2, the preform treated in step S4.1 is cured at 120°C for 4 hours, and then kept at 1100°C for 2 hours in a vacuum environment for cracking treatment.

[0041] Furthermore, in step S5.1, 4 vol.% of 4 μm diamond particles are added to the liquid polycarbosilane; the preform obtained in step S4 is immersed in the third slurry, maintained under vacuum conditions for 0.6 hours, and then pressurized, and taken out after maintaining the pressure at 0.8 MPa for 0.6 hours;

[0042] In step S5.2, curing is performed at a temperature of 150°C for 3 hours, and then the mixture is kept at 1000°C for 2 hours in a vacuum environment for cracking.

[0043] In step S6.1, the mass fraction of the phenolic resin solution is 30%, and the metal salt is nickel nitrate, and its mass is 2% of the phenolic resin powder;

[0044] In step S6.2, the vacuum condition is maintained for 0.6 hours, and then the pressure is increased and maintained at 0.8 MPa for 0.7 hours;

[0045] In step S6.3, the preform treated in step S6.2 is cured at 120°C for 3 hours, and then kept at 1000°C for 2 hours in a vacuum environment for cracking treatment;

[0046] In step S6.4, steps S6.2 to S6.3 are repeated for two rounds, and the preform is heat treated at 1550° C. for 2 hours in a vacuum environment;

[0047] In step S7, liquid silicon infiltration reaction is performed in a vacuum environment at 1500° C. for 120 minutes.

[0048] At the same time, the present invention provides a high thermal conductivity C f / SiC-ZrB 2-Diamond composite material preparation method prepared by high thermal conductivity C f / SiC-ZrB 2 -Diamond composite material.

[0049] Beneficial effects of the present invention:

[0050] 1. High thermal conductivity C of the present invention f / SiC-ZrB 2 -Diamond composite material preparation method: phenolic resin solution is used for resin-based slurry impregnation, and submicron ZrB is attached to the surface of the fiber bundle. 2 The ultra-high temperature ceramic layer composed of particles or silicon carbide particles can effectively alleviate the erosion of the metal melt on the fiber bundle. The high thermal conductivity C / SiC-ZrB2-Diamond composite material finally prepared has a strength of 257MPa, which ensures good thermal conductivity while ensuring strength.

[0051] 2. High thermal conductivity C of the present invention f / SiC-ZrB 2 -Diamond composite preparation method combines vacuum pressure impregnation and ultrasonic impregnation to introduce 2-5μm ZrB into the preform 2 particles and 3-6μm diamond particles, accurately constructed by large-size diamond particles and ZrB 2 The particles are the thermally conductive microstructure of the skeleton, and the diamond particles and ZrB are dispersed through the ultrasonic impregnation process. 2 particles to prevent them from settling, thereby forming a dispersed ultra-high temperature ceramic and diamond matrix.

[0052] 3. High thermal conductivity C of the present invention f / SiC-ZrB 2 -Diamond composite material preparation method adds diamond particles as a high thermal conductivity phase in liquid polycarbosilane (LPCS), and obtains a SiC layer (PIP-SiC layer) by a precursor conversion method between diamond and ZrB 2 A silicon carbide protective layer containing diamond particles is generated on the surface, which not only inhibits the erosion of the diamond particles by the metal melt, but also further increases the diamond content in the matrix, which can effectively improve the thermal conductivity of the composite material.

[0053] 4. High thermal conductivity C of the present invention f / SiC-ZrB 2 -Diamond composite material preparation method: adding metal salt to phenolic resin solution to modify the phenolic resin, and then the modified phenolic resin is carbonized by cracking treatment. D / I GThe graphitization rate of the modified phenolic resin was significantly reduced, indicating that its graphitization rate was significantly improved. Therefore, using the modified phenolic resin as the carbon source for the subsequent infiltration reaction (RMI) can effectively reduce the reaction rate of the metal melt and the resin to convert glassy carbon, and finally the high thermal conductivity C f / SiC-ZrB 2 -The thermal conductivity of Diamond composite material reaches 21.64W / (m·k).

[0054] 5. High thermal conductivity C of the present invention f / SiC-ZrB 2 -Diamond composite material preparation method heat treatment at 1500-1600℃ in a vacuum environment before RMI can effectively open the closed pores caused by the previous process (curing and cracking of modified phenolic resin, precursor conversion method), which is conducive to the densification of reactive infiltration. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 1 is a microscopic morphology image of the preform obtained in step 4 of Example 1 of the present invention; wherein (a) is a microscopic morphology image magnified 150 times, and (b) is a microscopic morphology image magnified 2000 times;

[0056] Figure 2 The high thermal conductivity C obtained in Example 1 of the present invention f / SiC-ZrB 2 - Flexural strength diagram of Diamond composites;

[0057] Figure 3 This is a microscopic morphology of the preform obtained in step nine of Example 1 of the present invention;

[0058] Figure 4 The infrared detection spectrum of the phenolic resin after carbonization modified in step 12 of Example 1 of the present invention is compared with the phenolic resin before carbonization; wherein (a) is the infrared spectrum of the phenolic resin before carbonization, and (b) is the infrared spectrum of the phenolic resin after carbonization modified in Example 1 of the present invention;

[0059] Figure 5 The high thermal conductivity C / SiC-ZrB obtained in Example 1 of the present invention 2 -Microscopic morphology of Diamond composite materials, where (a) is a microscopic morphology image magnified 500 times, and (b) is a microscopic morphology image magnified 1000 times. DETAILED DESCRIPTION

[0060] Embodiment 1

[0061] The present invention uses an ultrasonic impregnation method to introduce ZrB into a semi-dense fine-woven carbon fiber preform 2and diamond particles, generate a protective layer of silicon carbide and carbon on the diamond surface through polycarbosilane and modified phenolic resin, construct a liquid phase siliconization channel through the grading of particle size and solid content, and finally prepare C f / SiC-ZrB 2 -Diamond composite material, its thermal conductivity reaches 21.64W / (m·k).

[0062] The present invention provides a high thermal conductivity C f / SiC-ZrB 2 The preparation method of the diamond composite material specifically comprises the following steps:

[0063] Step 1: Deposit a pyrolytic carbon layer with a thickness of 300-600 nm on the finely woven and punctured carbon fiber preform by CVI process, and then deposit a SiC layer on the pyrolytic carbon layer by CVI process to obtain a semi-dense porous C f To ensure the strength of the preform, the thickness of the SiC layer is usually 1 to 4 μm.

[0064] In this embodiment, the thickness of the pyrolytic carbon layer is 500 nm, and the thickness of the SiC layer is 2-3 μm.

[0065] Step 2: weigh the phenolic resin powder and its solvent according to the ratio to prepare a phenolic resin solution with a mass fraction of 15%, and add ZrB with a particle size of 0.5 μm and a mass fraction of 5% of the phenolic resin solution to the prepared phenolic resin solution. 2 The particles are ball-milled for 12 hours to obtain a first slurry. The solvent of the phenolic resin powder is ethanol.

[0066] Step 3: In a pressure impregnation tank, the preform obtained in step 1 is suspended above the first slurry and vacuumed, and then the preform is immersed in the first slurry for impregnation, and the vacuum condition is maintained for 0.5 hours, and then the preform is inflated and pressurized, and taken out after maintaining the pressure at 0.8 MPa for 0.7 hours. The inflated and pressurized gas is usually filled with argon, nitrogen or air.

[0067] Step 4: The impregnated preform is cured at 120°C for 4 hours, and then kept at 1000°C for 2 hours in a vacuum environment for cracking. The obtained preform is as follows: Figure 1 As shown in (b), the surface of the carbon fiber is coated with resin carbon obtained by cracking phenolic resin and ZrB 2 (uhtc particles), Figure 1 (a) shows that there is no blockage in the pores, which facilitates filling of ultra-high temperature ceramics and diamond matrix in subsequent steps.

[0068] By adjusting the appropriate concentration of phenolic resin solution, ZrB 2The particle size and mass fraction of the particles are used to prepare the first slurry of appropriate concentration, and the viscosity of the phenolic resin solution is used to form a uniformly distributed resin carbon-ZrB on the fiber bundles in the preform during impregnation. 2 The shielding layer can effectively alleviate the corrosion of the metal melt and has higher strength. In other embodiments of the present invention, the ZrB in step 2 2 The particles can also be replaced with materials such as SiC to prepare the corresponding shielding layer.

[0069] Step 5: weigh the phenolic resin powder and its solvent according to the ratio, prepare a phenolic resin solution with a mass fraction of 15%, add ZrB with a particle size of 4 μm into the prepared phenolic resin solution. 2 particles and 4 μm diamond particles, stirred for 1 hour, and then ultrasonically treated for 1 hour, and the stirring and ultrasonic treatment were repeated once to obtain a second slurry, wherein ZrB 2 The volume ratio of ZrB particles to diamond particles is 1:1. 2 The total volume of the particles and the diamond particles accounted for 10 vol. % of the total volume of the second slurry.

[0070] Step 6: Place the second slurry in a beaker, and then place the beaker in a pressure impregnation tank. Hang the preform obtained in step 4 above the second slurry, seal the pressure impregnation tank and evacuate it, then immerse the preform in the second slurry, maintain the vacuum condition for 0.5 hours, then take out the preform including the beaker and place it in an ultrasonic disperser for ultrasonic impregnation and stirring for 20 minutes. Transfer the preform including the beaker to the pressure impregnation tank, seal it, inflate it and pressurize it, and take it out after maintaining the pressure at 0.9MPa for 0.5 hours.

[0071] Step seven, curing the preform processed in step six at 120° C. for 4 hours, and then maintaining the temperature at 1100° C. for 2 hours in a vacuum environment for cracking treatment, so as to achieve filling of the pores with dispersed ultra-high temperature ceramics and diamond matrix.

[0072] Step eight, add 4 vol.% of 4 μm diamond particles to liquid polycarbosilane (LPCS), stir and disperse to obtain a third slurry, suspend the preform treated in step seven above the third slurry in a pressure impregnation tank, evacuate the tank, and then immerse the preform in the third slurry, maintain the vacuum condition for 0.6 hours, then inflate and pressurize, and take out after maintaining the pressure at 0.8 MPa for 0.6 hours.

[0073] Step nine, placing the preform processed in step eight in a vacuum environment, controlling the temperature to 150°C, curing for 3 hours, and then maintaining the temperature at 1000°C for 2 hours in a vacuum environment for cracking treatment to convert the precursor into a silicon carbide protective layer containing diamond particles. The obtained preform structure is as follows: Figure 3As shown, the slurry impregnated particles are prepared by steps five to seven, including diamond and ZrB 2 .

[0074] Step ten, weigh phenolic resin powder and its solvent according to the ratio, prepare a phenolic resin solution with a mass fraction of 30%, weigh 2% nickel nitrate by mass of the phenolic resin powder, add it to the prepared phenolic resin solution, ultrasonically disperse for 30 minutes, and then continue stirring for 3 hours until the metal salt is completely dissolved to obtain a fourth slurry.

[0075] Step 11, suspend the preform processed in step 9 above the fourth slurry in a pressure impregnation tank and evacuate, then immerse the preform in the fourth slurry, maintain the vacuum condition for 0.6 hours, then inflate and pressurize, and take out after maintaining the pressure at 0.8 MPa for 0.7 hours.

[0076] Step 12, the preform treated in step 11 is cured at 120°C for 3 hours, and then kept at 1000°C for 2 hours in a vacuum environment for cracking treatment, and infrared detection is performed to obtain the infrared spectrum of the phenolic resin after the treatment in steps 10 to 12 as shown in Figure 4 As shown in (b), I D / I G is the intensity ratio of the D-peak and G-peak in the Raman characteristic peak of carbon atoms. Figure 4 (a) It can be seen that the present invention adds metal salt to modify the phenolic resin and then carbonizes it. D / I G Therefore, the graphitization rate is significantly improved after the phenolic resin is modified and then carbonized.

[0077] Step 13: Repeat steps 11 to 12 for 2 rounds, and then heat treat at 1550°C for 2 hours in a vacuum environment to obtain C / SiC-ZrB 2 -Diamond-C porous preform.

[0078] Step 14: Wrap the C / SiC-ZrB obtained in step 13 with silicon powder 2 -Diamond-C porous preform, then wrapped with graphite paper, and then C / SiC-ZrB 2 -The Diamond-C porous preform was placed in a siliconizing furnace and subjected to liquid silicon infiltration reaction for 120 minutes at 1500℃ in a vacuum environment to obtain a high thermal conductivity C / SiC-ZrB 2 -Diamond composite material, its microstructure is as follows Figure 5 As shown. For high thermal conductivity C / SiC-ZrB 2 -The flexural strength of the Diamond composite material was measured, and the results are as follows Figure 2As shown, the high thermal conductivity C / SiC-ZrB 2 -The flexural strength of Diamond composite material reaches 257MPa.

[0079] Embodiment 2

[0080] The present invention provides a high thermal conductivity C f / SiC-ZrB 2 The preparation method of the diamond composite material specifically comprises the following steps:

[0081] Step 1: deposit a 400 nm thick pyrolytic carbon layer on the fine-woven puncture preform by CVI process, and then deposit a SiC layer on the pyrolytic carbon layer by CVI process to obtain a semi-dense porous C f / SiC preform. In this embodiment, the thickness of the SiC layer is 3-4 μm.

[0082] Step 2: weigh phenolic resin powder and its solvent according to the ratio, prepare a phenolic resin solution with a mass fraction of 10%, add ZrB with a particle size of 0.1 μm and a mass fraction of 2% to the prepared phenolic resin solution. 2 The particles are ball-milled for 12 to 15 hours to obtain a first slurry. In this embodiment, the solvent of the phenolic resin powder is ethanol.

[0083] Step 3: In a pressure impregnation tank, the semi-dense porous C f The SiC preform is suspended above the first slurry and vacuumized, and then the preform is immersed in the first slurry for impregnation, and the vacuum condition is maintained for 1 hour, and then the preform is pressurized and taken out after maintaining the pressure at 0.5 MPa for 1 hour. In this embodiment, nitrogen is filled during the pressurization, and argon or air can also be filled in other embodiments of the present invention.

[0084] Step 4: The impregnated preform is cured at 150° C. for 2 hours, and then kept at 900° C. for 3 hours in a vacuum environment for cracking treatment to obtain a corresponding preform.

[0085] Step 5: weigh the phenolic resin powder and its solvent according to the ratio, prepare a phenolic resin solution with a mass fraction of 20%, add ZrB with a particle size of 5 μm into the prepared phenolic resin solution. 2 particles and 6 μm diamond particles, stirred for 1 hour, and then ultrasonically treated for 1.5 hours, and the stirring and ultrasonic treatment were repeated once to obtain a second slurry, wherein ZrB 2 The volume ratio of ZrB particles to diamond particles is 1:1. 2 The total volume of the particles and the diamond particles accounted for 6 vol.% of the total volume of the second slurry.

[0086] Step 6: Place the second slurry in a beaker, and then place the beaker in a pressure impregnation tank. Hang the preform obtained in step 4 above the second slurry, seal the pressure impregnation tank and evacuate it, then immerse the preform in the second slurry, maintain the vacuum condition for 0.8 hours, then take out the preform including the beaker and place it in an ultrasonic disperser for ultrasonic impregnation and stirring for 10 minutes. Transfer the preform including the beaker to the pressure impregnation tank, seal it, inflate it with air, and take it out after maintaining the pressure at 1.4MPa for 0.7 hours.

[0087] Step seven, curing the preform processed in step six at 100° C. for 6 hours, and then maintaining the temperature at 1200° C. for 1 hour in a vacuum environment for cracking treatment, so as to achieve filling of the pores with dispersed ultra-high temperature ceramics and diamond matrix.

[0088] Step eight, add 5 vol.% of 3μm diamond particles to liquid polycarbosilane (LPCS), stir and disperse to obtain a third slurry, suspend the preform treated in step seven above the third slurry in a pressure impregnation tank, evacuate the tank, and then immerse the preform in the third slurry, maintain the vacuum condition for 1 hour, then inflate and pressurize, and take out after maintaining the pressure at 0.5MPa for 1 hour.

[0089] Step nine, placing the preform processed in step eight in a vacuum environment, controlling the temperature to 120° C., curing for 6 hours, and then maintaining the temperature at 1200° C. for 1 hour in a vacuum environment for cracking treatment to convert the precursor into a silicon carbide protective layer containing diamond particles.

[0090] Step ten, weigh phenolic resin powder and its solvent according to the ratio, prepare a phenolic resin solution with a mass fraction of 40%, weigh nickel chloride with a mass fraction of 3% of the mass of the phenolic resin powder, add it to the prepared phenolic resin solution, ultrasonically disperse for 50 minutes, and continue stirring for 6 hours until the metal salt is completely dissolved to obtain a fourth slurry.

[0091] Step 11, suspend the preform processed in step 9 above the fourth slurry in a pressure impregnation tank and evacuate, then immerse the preform in the fourth slurry, maintain the vacuum condition for 1 hour, then inflate and pressurize, and take out after maintaining the pressure at 1.4 MPa for 0.5 hour.

[0092] Step 12: The preform processed in step 11 is cured at 150° C. for 6 hours, and then kept at 1200° C. for 1 hour in a vacuum environment for cracking treatment.

[0093] Step 13: Repeat steps 11 to 12 for one round, and then heat treat at 1500°C for 1 hour in a vacuum environment to obtain C / SiC-ZrB 2 -Diamond-C porous preform.

[0094] Step 14: Wrap the C / SiC-ZrB obtained in step 13 with silicon powder 2 -Diamond-C porous preform, then wrapped with graphite paper, and then C / SiC-ZrB 2 -The Diamond-C porous preform was placed in a siliconizing furnace and subjected to liquid silicon infiltration reaction at 1550℃ vacuum environment for 90 minutes to obtain a high thermal conductivity C / SiC-ZrB 2 -Diamond composite material, completed preparation.

[0095] Embodiment 3

[0096] The present invention provides a high thermal conductivity C f / SiC-ZrB 2 The preparation method of the diamond composite material specifically comprises the following steps:

[0097] Step 1: a pyrolytic carbon layer with a thickness of 600 nm is deposited on the fine-woven puncture preform by CVI process, and then a SiC layer is deposited on the pyrolytic carbon layer by CVI process to obtain a semi-dense porous C f / SiC preform. In this embodiment, the thickness of the SiC layer is 1-2 μm.

[0098] Step 2: weigh the phenolic resin powder and its solvent according to the ratio, prepare a phenolic resin solution with a mass fraction of 20%, add ZrB with a particle size of 1 μm and a mass fraction of 15% to the prepared phenolic resin solution. 2 The particles are ball-milled for 12 hours to obtain a first slurry. In this embodiment, the solvent of the phenolic resin powder is acetone.

[0099] Step 3: In a pressure impregnation tank, the semi-dense porous C f The SiC preform is suspended above the first slurry and evacuated, and then the preform is immersed in the first slurry for impregnation, and the vacuum condition is maintained for 0.75 hours, and then argon is filled and pressurized, and the preform is taken out after maintaining the pressure at 1.4 MPa for 0.5 hours.

[0100] Step 4: Curing the impregnated preform at 100° C. for 6 hours, and then maintaining the temperature at 1200° C. for 1 hour in a vacuum environment for cracking treatment to obtain a corresponding preform.

[0101] Step 5: weigh the phenolic resin powder and its solvent according to the ratio, prepare a phenolic resin solution with a mass fraction of 30%, add ZrB with a particle size of 2 μm into the prepared phenolic resin solution. 2 particles and 3 μm diamond particles, stirred for 1.5 hours, and then ultrasonically treated for 1 hour, and the stirring and ultrasonic treatment were repeated once to obtain a second slurry, wherein ZrB 2 The volume ratio of ZrB particles to diamond particles is 1:1.2 The total volume of the particles and diamond particles accounted for 12 vol. % of the total volume of the second slurry.

[0102] Step 6: Place the second slurry in a beaker, and then place the beaker in a pressure impregnation tank. Hang the preform obtained in step 4 above the second slurry, seal the pressure impregnation tank and evacuate it, then immerse the preform in the second slurry, maintain the vacuum condition for 1 hour, then take out the preform including the beaker and place it in an ultrasonic disperser for ultrasonic impregnation and stirring for 30 minutes. Transfer the preform including the beaker to the pressure impregnation tank, seal it, inflate it with air, and take it out after maintaining the pressure at 0.5MPa for 1 hour.

[0103] Step seven, curing the preform processed in step six at 120° C. for 2 hours, and then maintaining the temperature at 900° C. for 3 hours in a vacuum environment for cracking treatment, so as to achieve filling of the pores with dispersed ultra-high temperature ceramics and diamond matrix.

[0104] Step eight, add 2 vol.% of 5 μm diamond particles to liquid polycarbosilane (LPCS), stir and disperse to obtain a third slurry, suspend the preform treated in step seven above the third slurry in a pressure impregnation tank, evacuate, and then immerse the preform in the third slurry, maintain the vacuum condition for 0.5 hour, then inflate and pressurize, and take out after maintaining the pressure at 1.4 MPa for 0.5 hour.

[0105] Step nine, placing the preform processed in step eight in a vacuum environment, controlling the temperature to 180°C, curing for 2 hours, and then maintaining the temperature at 900°C for 3 hours in a vacuum environment for cracking treatment to convert the precursor into a silicon carbide protective layer containing diamond particles.

[0106] Step ten, weigh phenolic resin powder and its solvent according to the ratio, prepare a phenolic resin solution with a mass fraction of 20%, weigh 5% of the mass of copper nitrate of the phenolic resin powder, add it to the prepared phenolic resin solution, ultrasonically disperse for 10 minutes, and then continue stirring for 2 hours until the metal salt is completely dissolved to obtain a fourth slurry.

[0107] Step 11, suspend the preform processed in step 9 above the fourth slurry in a pressure impregnation tank and evacuate, then immerse the preform in the fourth slurry, maintain the vacuum condition for 0.5 hours, then inflate and pressurize, and take out after maintaining the pressure at 0.5 MPa for 1 hour.

[0108] Step 12: The preform processed in step 11 is cured at 100° C. for 2 hours, and then kept at 900° C. for 3 hours in a vacuum environment for cracking treatment.

[0109] Step 13: Repeat Step 11 to Step 12 for 3 rounds, and then heat treat at 1600°C for 3 hours in a vacuum environment to obtain C / SiC-ZrB 2 -Diamond-C porous preform.

[0110] Step 14: Wrap the C / SiC-ZrB obtained in step 13 with silicon powder 2 -Diamond-C porous preform, then wrapped with graphite paper, and then C / SiC-ZrB 2 -The Diamond-C porous preform was placed in a siliconizing furnace and subjected to liquid silicon infiltration reaction for 30 minutes at 1600℃ vacuum environment to obtain high thermal conductivity C / SiC-ZrB 2 -Diamond composite material, completed preparation.

Claims

1. A high thermal conductivity C f / SiC-ZrB2-Diamond composite material preparation method, characterized in that: The following steps are involved: S1, a pyrolytic carbon layer and a SiC layer are sequentially deposited on the prepared preform to obtain a semi-dense porous C f / SiC preform; S2, adding ZrB2 particles or SiC particles to the phenolic resin solution, and ball milling to obtain a first slurry; S3, using the first slurry to treat the semi-dense porous C obtained in step S1 f / SiC preform is subjected to vacuum pressure impregnation, curing and cracking treatment in sequence; S4, using the preform treated by the second slurry in step S3 to perform ultrasonic impregnation, curing and cracking treatment in sequence to obtain a preform filled with ultra-high temperature ceramics and a diamond matrix; the second slurry is obtained by adding ZrB2 particles and diamond particles to a phenolic resin solution and mixing them uniformly; S5, preparing a silicon carbide protective layer containing diamond particles on the surface of the ultra-high temperature ceramic and diamond substrate filled in the preform; S6, immersing the preform treated in step S5 into a phenolic resin solution modified with a metal salt, then taking it out and carbonizing it to obtain a C / SiC-ZrB2-Diamond-C porous preform; the metal salt is a nickel-containing metal salt or a copper-containing metal salt; S7, performing liquid silicon infiltration reaction on the C / SiC-ZrB2-Diamond-C porous preform obtained in step S6 to obtain a high thermal conductivity C f / SiC-ZrB2-Diamond composite material is prepared.

2. According to claim 1, the high thermal conductivity C f / SiC-ZrB2-Diamond composite material preparation method, characterized in that: Step S5 is specifically as follows: S5.1, adding 2-5 vol.% of 3-5 μm diamond particles to liquid polycarbosilane, stirring and dispersing to obtain a third slurry, immersing the preform obtained in step S4 into the third slurry under vacuum conditions, maintaining the vacuum conditions for 0.5-1 hour, then pressurizing, and taking out after maintaining the pressure at 0.5 MPa-1.4 MPa for 0.5-1 hour; S5.2, curing the preform processed in step S5.1 in a vacuum environment at a temperature of 120-180° C. for 2-6 hours, and then maintaining the temperature at 900-1200° C. for 1-3 hours in a vacuum environment for cracking treatment.

3. According to claim 2, the high thermal conductivity C f / SiC-ZrB2-Diamond composite material preparation method, characterized in that: Step S6 is specifically as follows: S6.1, using phenolic resin powder and its solvent to prepare a phenolic resin solution with a mass fraction of 20%-50%, adding a metal salt with a mass fraction of 1%-5% of the phenolic resin powder, stirring until the metal salt is completely dissolved, to obtain a fourth slurry; the solvent is ethanol or acetone; the metal salt is nickel chloride, cupric chloride, nickel nitrate or cupric nitrate; S6.2, immersing the preform treated in step S5 into the fourth slurry under vacuum conditions, maintaining the vacuum conditions for 0.5-1 hour, then pressurizing, and taking out after maintaining the pressure at 0.5 MPa-1.4 MPa for 0.5-1 hour; S6.3, curing the preform treated in step S6.2 at 100-150° C. for 2-6 hours, and then maintaining the temperature at 900-1200° C. for 1-3 hours in a vacuum environment for cracking treatment; S6.4, repeat 1-3 rounds of steps S6.2 to S6.3, and then heat treat the preform at 1500-1600°C for 1-3 hours in a vacuum environment to obtain a C / SiC-ZrB2-Diamond-C porous preform.

4. The high thermal conductivity C according to claim 3 f / SiC-ZrB2-Diamond composite material preparation method, characterized in that: Step S7 is specifically as follows: The C / SiC-ZrB2-Diamond-C porous preform obtained in step S6 is wrapped with silicon powder and then wrapped with graphite paper. Thereafter, the C / SiC-ZrB2-Diamond-C porous preform is placed in a siliconizing furnace and subjected to liquid silicon infiltration reaction for 30-120 minutes in a vacuum environment of 1500-1600°C to obtain a high thermal conductivity C / SiC-ZrB2-Diamond composite material, thereby completing the preparation.

5. The high thermal conductivity C according to claim 4 f / SiC-ZrB2-Diamond composite material preparation method, characterized in that: Step S3 is specifically as follows: S3.1, under vacuum conditions, the semi-dense porous C f / The SiC preform is immersed in the first slurry, and the vacuum condition is maintained for 0.5-1 hour, and then pressurized, and taken out after maintaining the pressure at 0.5MPa-1.4MPa for 0.5-1 hour; S3.2, curing the impregnated preform at 100-150° C. for 2-6 hours, and then maintaining the temperature at 900-1200° C. for 1-3 hours in a vacuum environment for cracking treatment.

6. The high thermal conductivity C according to claim 5 f / SiC-ZrB2-Diamond composite material preparation method, characterized in that: Step S4 is specifically as follows: S4.1, under vacuum conditions, immerse the preform treated in step S3.2 into the second slurry for 0.5-1 hour, place the preform and the second slurry together in an ultrasonic disperser for ultrasonic immersion and stirring for 10-30 minutes, transfer the preform and the second slurry together to a pressure impregnation tank, seal and pressurize, and take out after maintaining a pressure of 0.5MPa-1.4MPa for 0.5-1 hour; The second slurry is obtained by adding ZrB2 particles and diamond particles into a phenolic resin solution and mixing them uniformly; S4.2, curing the preform treated in S4.1 at 100-150°C for 2-6 hours, and then maintaining the temperature at 900-1200°C for 1-3 hours in a vacuum environment for cracking to obtain a preform filled with ultra-high temperature ceramics and a diamond matrix.

7. The high thermal conductivity C according to claim 6 f / SiC-ZrB2-Diamond composite material preparation method, characterized in that: In step S4, the preparation method of the second slurry is specifically as follows: Phenolic resin powder and its solvent are weighed respectively according to the ratio to prepare a phenolic resin solution with a mass fraction of 15%-30%, wherein the solvent is ethanol or acetone, ZrB2 particles with a particle size of 2-5 μm and diamond particles with a particle size of 3-6 μm are added to the phenolic resin solution, stirred for 1-1.5 hours, and then ultrasonically treated for 1-1.5 hours, and the stirring and ultrasonic treatment are repeated to obtain a second slurry, wherein the volume ratio of ZrB2 particles to diamond particles is 1:1, and the total volume of ZrB2 particles and diamond particles accounts for 6-12 vol.% of the total volume of the second slurry; In step S1, the thickness of the pyrolytic carbon layer is 300-600 nm; the thickness of the SiC layer is 1-4 μm; In step S2, the particle size of ZrB2 or SiC is 0.1-1 μm, and the mass is 2%-15% of the phenolic resin solution; the mass fraction of the phenolic resin solution is 10%-20%, and the solvent is ethanol or acetone.

8. The high thermal conductivity C according to claim 7 f / SiC-ZrB2-Diamond composite material preparation method, characterized by: In step S1, the thickness of the pyrolytic carbon layer is 500 nm, and the thickness of the SiC layer is 2-3 μm; In step S2, the mass fraction of the phenolic resin solution is 15%, and ZrB2 particles are added to the phenolic resin solution, the particle size of the ZrB2 particles is 0.5 μm, and the mass is 5% of the phenolic resin solution; In step S3.1, the vacuum condition is maintained for 0.5 hours, and then pressurized, and the pressure is maintained at 0.8 MPa for 0.7 hours before being taken out; In step S3.2, the impregnated preform is cured at 120°C for 4 hours, and then kept at 1000°C for 2 hours in a vacuum environment for cracking treatment; In step S4.1, the preform treated in step S3.2 is immersed in the second slurry for 0.5 hours, the preform and the second slurry are placed in an ultrasonic disperser for ultrasonic immersion and stirring for 20 minutes, the preform and the second slurry are transferred to a pressure impregnation tank, sealed and pressurized, and taken out after maintaining a pressure of 0.9 MPa for 0.5 hours; In step S4.2, the preform treated in step S4.1 is cured at 120°C for 4 hours, and then kept at 1100°C for 2 hours in a vacuum environment for cracking treatment.

9. The high thermal conductivity C according to claim 8 f / SiC-ZrB2-Diamond composite material preparation method, characterized by: In step S5.1, 4 vol.% of 4 μm diamond particles are added to liquid polycarbosilane; the preform obtained in step S4 is immersed in the third slurry, maintained under vacuum conditions for 0.6 hours, then pressurized, and taken out after maintaining the pressure at 0.8 MPa for 0.6 hours; In step S5.2, curing is performed at a temperature of 150°C for 3 hours, and then the mixture is kept at 1000°C for 2 hours in a vacuum environment for cracking. In step S6.1, the mass fraction of the phenolic resin solution is 30%, and the metal salt is nickel nitrate, and its mass is 2% of the phenolic resin powder; In step S6.2, the vacuum condition is maintained for 0.6 hours, and then the pressure is increased and maintained at 0.8 MPa for 0.7 hours; In step S6.3, the preform treated in step S6.2 is cured at 120°C for 3 hours, and then kept at 1000°C for 2 hours in a vacuum environment for cracking treatment; In step S6.4, steps S6.2 to S6.3 are repeated for two rounds, and the preform is heat treated at 1550° C. for 2 hours in a vacuum environment; In step S7, liquid silicon infiltration reaction is performed in a vacuum environment at 1500° C. for 120 minutes.

10. A high thermal conductivity C according to any one of claims 1 to 9 f High thermal conductivity C / SiC-ZrB2-Diamond composite material preparation method f / SiC-ZrB2-Diamond composite material.

Citation Information

Patent Citations

  • Preparation method of C / SiC-ZrB2-ZrC ultrahigh-temperature ceramic-based composite material

    CN102515870A

  • Construction method for directional heat conduction channel of high-thermal-conductivity diamond modified silicon carbide ceramic matrix composite material

    CN109704776A

  • Carbon fiber-ultrahigh-temperature ceramic composite material and preparation method thereof

    CN118063230A

  • Method for preparing carbon-ceramic brake material and method for preparing carbon-ceramic brake disc

    WO2017107735A1

Cited By

  • C / SiC-ZrB2-HfB2-Cu composite material and preparation method thereof

    CN122102699A